Transcription factor MaMADS36 plays a central role in regulating banana fruit ripening. (19th July 2021) - Liu, Juhua; Liu, Mengting; Wang, Jingyi; Zhang, Jing; Miao, Hongxia; Wang, Zhuo; Jia, Caihong; Zhang, Jianbin; Xu, Biyu; Jin, Zhiqiang
Abstract : In banana ripening, the transcription factor MaMADS36 interacts with 74 other proteins to form a co-expression network, acting as a switch to regulate ethylene biosynthesis, starch degradation, softening, and sugar accumulation. Abstract: Bananas are model fruits for studying starch conversion and climactericity. Starch degradation and ripening are two important biological processes that occur concomitantly in banana fruit. Ethylene biosynthesis and postharvest fruit ripening processes, i.e. starch degradation, fruit softening, and sugar accumulation, are highly correlated and thus could be controlled by a common regulatory switch. However, this switch has not been identified. In this study, we transformed red banana ( Musa acuminata L.) with sense and anti-sense constructs of the MaMADS36 transcription factor gene (also MuMADS1, Ma05_g18560.1). Analysis of these lines showed that MaMADS36 interacts with 74 other proteins to form a co-expression network and could act as an important switch to regulate ethylene biosynthesis, starch degradation, softening, and sugar accumulation. Among these target genes, musa acuminata beta-amylase 9b ( MaBAM9b, Ma05_t07800.1), which encodes a starch degradation enzyme, was selected to further investigate the regulatory mechanism of MaMADS36. Our findings revealed that MaMADS36 directly binds to the CA/T(r)G box of the MaBAM9b promoter to increase MaBAM9b transcription and, in turn, enzyme activity and starch degradation during ripening. These results will further our understanding of the fine regulatory mechanisms of MADS-box transcription factors in regulating fruit ripening, which can be applied to breeding programs to improve fruit shelf-life.